The contingencies of Chinese diasporic identities in Charlson Ong’s speculative fiction - Velasco, Joseph Ching (Animo Repository, 2017)
Charlson Ong’s award-winning novel An Embarrassment of Riches (2000) creatively narrates the history of the Chinese diaspora as an overdetermined event in the Southeast Asian Region. The novel explores the politics of belonging, displacement, identity, and territory through a/n (re)imagined nation built primarily on Philippine historical and cultural contingencies. This essay seeks to explore the junctures and vicissitudes of the Chinese diaspora in the region through the following questions: How is hybridity manifested by selected characters and other cultural elements in the narrative? Second, how do the perceptions of homeland, marked by ambivalence and contradiction, operate in the narrative? And third, how does the memory of the characters’ homeland or the lack of it contribute to identity formation? Furthermore, an analysis of the novel’s form has been conducted, possibly asserting the notion that the genre is also a hybridized entity. This paper illustrates the complexity of the Chinese diaspora in the region and its bearing to identity formation. © Ateneo de Manila University.